2022
DOI: 10.1002/mnfr.202200377
|View full text |Cite
|
Sign up to set email alerts
|

Prumnopitys Andina Fruit Extract Activates Liver X Receptors after In Vitro Digestion

Abstract: Scope: 20-Hydroxyecdysone (20E) is the main phytochemical present in the fresh arils of Prumnopitys andina. 20E is reported to have anabolic effects by modulation of gene transcription by interaction with nuclear receptors. Our aim is to evaluate the in vitro bioaccessibility, transepithelial transport of 20E, and the capacity of P. andina fruit extract and 20E to activate selected mammalian nuclear receptors in transiently transfected human cells after simulated gastrointestinal digestion. Results: 20E shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…Jimenez-Aspee et al [52] prepared a Prumnopitys andina fruit extract and identified a series of phenolic compounds, including derivatives of hydroxycinnamic acids and flavonoids like shikimic acid, protocatechuic acid, caffeic acid, ferulic acid, apigenin, isorhamnetin, and quercetin (among others). These extracts were then used to determine whether they would affect the transcription of LXRα or LXRβ in HepG2 cells.…”
Section: Phenolic Extractsmentioning
confidence: 99%
“…Jimenez-Aspee et al [52] prepared a Prumnopitys andina fruit extract and identified a series of phenolic compounds, including derivatives of hydroxycinnamic acids and flavonoids like shikimic acid, protocatechuic acid, caffeic acid, ferulic acid, apigenin, isorhamnetin, and quercetin (among others). These extracts were then used to determine whether they would affect the transcription of LXRα or LXRβ in HepG2 cells.…”
Section: Phenolic Extractsmentioning
confidence: 99%